Freshwater algae Cladophora glomerata and Vaucheria sp. from Serbia as sources of bioactive compounds: chemical analysis and biological activities - Stefanović, Olgica D.; Rakonjac, Aleksandra B.; Nikodijević, Danijela D.; Milojević, Sara D.; Dinić, Anica; Simić, Snežana B. (Archives of Biological Sciences, 2024)
Paper description: There is growing interest in novel sources of biologically active compounds, including freshwater macroalgae whose bioactivities are largely unexplored. Ethanol and acetone extracts of Cladophora glomerata and Vaucheria were prepared. Total phenolic and pigment contents were determined. In vitro bioactivities, including antioxidant potential, antimicrobial, antibiofilm activities, and cytotoxicity were examined. glomerata and Vaucheria sp. extracts are a valuable source of bioactive compounds. Abstract: We examined potential biological activities of two taxa of freshwater algae, Cladophora glomerata and Vaucheria sp., from Serbia. The total phenolic and pigment contents, antioxidant potential, antimicrobial, antibiofilm activities, and cytotoxicity of the ethanol and acetone extracts were evaluated. The extracts were also subjected to Fourier transform infrared spectroscopy (FTIR) analysis. The levels of total phenolic compounds, chlorophylls a and b, and carotenoids varied based on both the algal taxa and the type of extracts. FTIR analysis showed the presence of lipids, unsaturated fatty acids, protein, carbohydrates, and phenols in the algal extracts. The extracts had moderate DPPH radical scavenging activity and lower reducing power compared with ascorbic acid. The antimicrobial activity expressed as minimum inhibitory concentrations ranged from 0.31 mg/mL to 10 mg/mL. The strains of Staphylococcus aureus and Bacillus cereus isolated from food samples, as well as S. aureus ATCC 25923, were the most sensitive. For the first time, the antibiofilm activity test revealed 98.7% inhibition of S. aureus biofilm formation. The extracts exhibited cytotoxic effects on choriocarcinoma JAR cells but without selectivity on normal fetal lung fibroblast MRC-5 cells. This is the first report on the biological activities of freshwater macroalgae from Serbia.